Muscle Fiber Typing in Bovine and Porcine Skeletal Muscles Using Immunofluorescence with Monoclonal Antibodies Specific to Myosin Heavy Chain Isoforms - Song, Sumin (Food Sci Anim Resour, 2020)
The aim of this study was to optimize staining procedures for muscle fiber typing efficiently and rapidly in bovine and porcine skeletal muscles, such as longissimus thoracis, psoas major, semimembranosus, and semitendinosus muscles. The commercially available monoclonal anti-myosin heavy chain (MHC) antibodies and fluorescent dye-conjugated secondary antibodies were applied to immunofluorescence histology. Two different procedures, such as cocktail and serial staining, were adopted to immunofluo-rescence analysis. In bovine muscles, three pure types (I, IIA, and IIX) and one hybrid type, IIA+IIX, were identified by the cocktail procedure with a combination of BA-F8, SC-71, BF-35, and 6H1 anti-MHC antibodies. Porcine muscle fibers were typed into four pure types (I, IIA, IIX, and IIB) and two hybrid types (IIA+IIX and IIX+IIB) by a serial procedure with a combination of BA-F8, SC-71, BF-35, and BF-F3. Unlike for bovine muscle, the cocktail procedure was not recommended in porcine muscle fiber typing because of the abnormal reactivity of SC-71 antibody under cocktail procedure. Within the four antibodies, combinations of two or more anti-MHC antibodies allowed us to distinguish pure fiber types or all fiber types including hybrid types. Application of other secondary antibodies conjugated with different fluorescent dyes allowed us to get improved image resolution that clearly distinguished hybrid fibers. Muscle fiber characteristics differed depending on species and muscle types.